2014
DOI: 10.1519/jsc.0b013e3182a1f44c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plyometric Training on Endurance and Explosive Strength Performance in Competitive Middle- and Long-Distance Runners

Abstract: The purpose of this study was to examine the effect of a short-term plyometric training program on explosive strength and endurance performance in highly competitive middle- and long-distance runners. Athletes were randomly assigned to a control group (CG, n = 18, 12 men) and an explosive strength training group (TG, n = 18, 10 men). Drop jump (DJ) from 20 (DJ20) and 40 cm (DJ40), countermovement jump with arms (CMJA), 20-m sprint time, and 2.4-km endurance run time test were carried out before and after 6 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
110
3
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(129 citation statements)
references
References 28 publications
10
110
3
6
Order By: Relevance
“…This parameter is significantly correlated with the distance covered per game (Haugen et al, 2014). The efficacy of repeated sprints is also reflected in the reduction of energy costs, which leads us to talk about the running economy that has a proportional relationship with the VO2max and the anaerobic threshold (Gist et al, 2014) and these parameters are important factor for endurance (Ramírez-Campillo et al, 2014;Macpherson et al, 2015). Improving aerobic performance is proportional to the total distance game with a doubling of number of sprints during competition .…”
Section: Discussionmentioning
confidence: 99%
“…This parameter is significantly correlated with the distance covered per game (Haugen et al, 2014). The efficacy of repeated sprints is also reflected in the reduction of energy costs, which leads us to talk about the running economy that has a proportional relationship with the VO2max and the anaerobic threshold (Gist et al, 2014) and these parameters are important factor for endurance (Ramírez-Campillo et al, 2014;Macpherson et al, 2015). Improving aerobic performance is proportional to the total distance game with a doubling of number of sprints during competition .…”
Section: Discussionmentioning
confidence: 99%
“…One of the methods used for training jumps is plyometric training, which is the use of exercises that enhance the use of muscle stretch-shortening cycle (SSC) by conducting an intense eccentric action immediately followed by a rapid concentric action 1 . Recent studies have shown the effectiveness of plyometric training for the improvement of performance variables such as agility 2 , speed 3 , power and height of vertical jumps 4 , strength and explosive power of the lower limbs 5 . Plyometric training sessions use different types of jumps such as drop jumps, sequential jumps, unilateral jumps, jumps over obstacles, side jumps, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies describe plyometric training as containing activities like jumping, hopping, ball-throwing, skipping, obstacle jumps, while according to other studies, it comprises resistance activities, a harmony of the leg with other limbs, speed skills, speed sports, throwing, power, and balance [4]. As a result, a good way to improve plyometric training is to use resistance training [5].…”
Section: Introductionmentioning
confidence: 99%